Comparative Advertisings from Marketing Perspective - Aydın, İbrahim (Muş Alparslan Üniversitesi, 2017)
The purpose of the study is to explain basic concepts of comparative advertising through marketing perspective. After the near future removal of the formal barriers against direct comparative advertising in Turkey, it will begin to appear at different mediums. There are different types of comparative advertising, such as direct comparative advertising and, indirect comparative advertising. Comparative advertisements were firstly appeared in the 1900s and legal obstacles with regard to use of direct comparative advertising were removed in United States by 1971. Direct comparative advertising has both advantages and disadvantages. When compared to non-comparative advertising, positive aspects of direct comparative advertising are informing and persuading the consumer, helping the consumer to make better comparisons among competing brands, encouraging competition, improving product features, helping to reduce the market barriers for newcomers.  Yet there are also negative aspects to it such as, it is more likely to cause consumer confusion and to reduce honesty and impartiality and also it is more likely to cause fierce competition against companies and increase the number of bad attitudes regarding advertisement, if it is used carelessly it can result in legal ramifications. There are need points to pay attention when using comparative ads to avoid adverse events.

Bu çalışmanın amacı, pazarlama bakışı açısı ile karşılaştırmalı reklamların temel kavramlarını açıklamaktır. Türkiye’de doğrudan karşılaştırmalı reklama yönelik yasal engellerin yakın gelecekte kalkacak olmasıyla beraber çeşitli medyalarda doğrudan karşılaştırmalı reklamlarla karşılaşılacaktır. Karşılaştırmalı reklamların, doğrudan karşılaştırmalı, dolaylı karşılaştırmalı gibi farklı türleri bulunmaktadır. 1900’lü yıllarda kullanılmaya başlandığına rastlanmış ve 1971 yılında da doğrudan karşılaştırmalı reklamın Amerika’da yapılabilmesine yönelik hukuki engeller kaldırılmıştır. Karşılaştırmalı olmayan reklama kıyasla, bilgilendirme, ikna etme, rakip markalar arasında daha iyi kıyaslama olanağı sağlama, tüketici lehine rekabeti teşvik etme, ürünlerin geliştirilmesine etkisi olma, pazara yeni girecek firma için pazara giriş bariyerlerini azaltma gibi olumlu yönlerinin yanında, tüketicide kafa karışıklığına neden olması, doğruluk ve tarafsızlığın kaybedilmesi, reklama yönelik daha fazla olumsuz tutumlara neden olması, firmaların aleyhine şiddetli rekabete neden olması, dikkatli kullanılmadığı zaman yasal risklerinin olması gibi olumsuz yönleri de mevcuttur. Olumsuzluklarla karşılaşılmaması için karşılaştırmalı reklamlar kullanılırken dikkat edilmesi gereken noktalar bulunmaktadır.
Pazarlama Perspektifinden Karşılaştırmalı Reklamlar
anemon
Keywords: Direct Comparative Advertising; Permission to Use; Marketing; Comparative Advertisement; Doğrudan Karşılaştırmalı Reklam; Kullanım İzni; Pazarlama; Karşılaştırmalı Reklam